Vitamin E and Donepezil for the Treatment of Mild Cognitive Impairment - Petersen, Ronald C.; Thomas, Ronald G.; Kaye, Jeffrey; Sano, Mary (New England Journal of Medicine, 2005)
Mild cognitive impairment is a transitional state between the cognitive changes of normal aging and early Alzheimer’s disease. In a double-blind study, we evaluated subjects with the amnestic subtype of mild cognitive impairment. Subjects were randomly assigned to receive 2000 IU of vitamin E daily, 10 mg of donepezil daily, or placebo for three years. The primary outcome was clinically possible or probable Alzheimer’s disease; secondary outcomes were cognition and function.